Studying elites old and new: : Elites in a Digitizing Society (Intercom - Brazilian Journal of Communication Sciences, 2026)
This contribution discusses ways of sampling, recruiting, and interviewing members of various types of elites in the digital age. Enlisting tried and true examples from research on the larger literature on elites, the article shows how various recruitment and interviewing strategies may be adapted to take advantage of contemporary digital platforms in order to identify and recruit individuals who are not tied to particular workplaces or organizations. It also shows how particular recruitment and data collection procedures are suited to more traditional kinds of digital elites, namely professional digital elites, as well as the more elusive elites who populate contemporary content creation and gig platforms.
Keywords: Digital elites, research design, recruitment, methods, interviewing